Subrogation and Confiscatory Premiums. An Examination of the Contractual Right to Subrogation and Whether Anti-subrogation Statutes Should Be Enacted in Uganda - Patricia Kyakuhaire (Uganda Christian University, 2024)
This dissertation presents the results of the research study on subrogation and confiscatory premiums in Uganda. This study is aimed at analyzing the contractual right to subrogation and whether anti-subrogation statutes should be enacted in the country. The study is majorly founded on insurance law which is contract based. Insurance is a contract under which one party known as the insurer in exchange for a premium, agrees with another party known as the policy holder to make a payment, or provide a benefit to the policy holder or another person on the occurrence of a specified uncertain event which if it occurs, will be adverse to the interests of the policy holder or to the interests of a person who will receive the payment or benefit , as elaborated in the case of Prudential Insurance Company V Commissioners of Inland Revenue . Insurance like any other contract involves two parties that include the insured who pays premium and passes on the risk to the insurer who is usually the insurance company. The general principle is that once a peril occurs that is insured, the insured must be fully indemnified before the insurer can subrogate , and this right is only enjoyed by the insurer. Subrogation is a substitution of one person for another, so that the same rights and duties which were attached to the original are attached to that third party . However, subrogation moves in handy with payment of premiums which are usually non-refundable. Confiscatory premiums are those premiums taken by an authority of law compulsorily as long as one agrees to enter an insurance contract. Insurance contracts are non-profit making contracts but this rule seemingly applies to the insured and not the insurance company (insurer), and this makes it an unfair concept. This research therefore intends to analyze the impact of confiscatory premiums on the insured and insurer. It will also point out some recommendations that will improve on the knowledge gap in insurance law. Some of these recommendations include promoting equality and equity. Others are sensitization of masses, enactment of new laws and amendment of some of the existing laws that seem to be bent to one side, in relation to subrogation in Insurance in Uganda.